The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.3390/i2060281
|View full text |Cite
|
Sign up to set email alerts
|

Four-Reference State-Specific Brillouin-Wigner Coupled-Cluster Method: Study of the IBr Molecule

Abstract: Abstract:We implemented the state-specific Brillouin-Wigner coupled-cluster method for the complete model space spanned by four reference configurations generated by two electrons in two active orbitals. We applied the method (together with the previously suggested a posteriori size-extensivity correction) to the calculation of spectroscopic constants of the IBr molecule, using averaged relativistic effective core potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…This is done in the last CC iteration, and this elimination may be viewed therefore as an a posteriori size‐extensivity correction. Application of this correction was successful in restoring almost a full size‐extensivity in quasidegenerate systems of different structure 7–10.…”
Section: Introductionmentioning
confidence: 99%
“…This is done in the last CC iteration, and this elimination may be viewed therefore as an a posteriori size‐extensivity correction. Application of this correction was successful in restoring almost a full size‐extensivity in quasidegenerate systems of different structure 7–10.…”
Section: Introductionmentioning
confidence: 99%
“…An efficient implementation of this method has been developed 14 and later extended for a number of reference configurations and open shell ones. 15,16 Hubač and Wilson formulated a simple a posteriori sizeextensivity correction for the BWCC method, 17 which turned out to work surprisingly well. 18 Moreover, we have shown that one can construct continuous transitions between multireference ͑MR͒ BWCC and other Hilbert space multireference coupled-cluster ͑MRCC͒ approaches and on this basis one can perform an iterative size-extensivity correction, which yields exact extensivity.…”
Section: Introductionmentioning
confidence: 97%
“…19 The performance of the BWCC method has been assessed by calculations on several small, but "difficult" model systems and diatomic molecules. 15,16,[20][21][22][23][24][25] The efficacy of the implementation 14 and the elimination of the intruder-state problem in BWCC have been demonstrated by calculations of chemically interesting systems of moderate size. [26][27][28][29] Recent reviews of the BWCC theory can be found in Refs.…”
Section: Introductionmentioning
confidence: 98%
“…In view of its desirable property of a fast convergence, thanks to the BW energy denominator shifts which simultaneously enable to avoid intruder states, as well as to the size-extensivity corrections, the basic BW CCSD method has yielded reasonably accurate results for systems in which the nondynamic correlation plays a significant role [143][144][145][146][147][148][149][150][151][152][153][154][155]. Recently, the connected triple excitations have been included in the MR BWCC theory [157][158][159], resulting in a considerable increase in the accuracy of the method thanks to a more precise description of dynamical correlation effects, similarly as in the SR case.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, an a posteriori size-extensivity correction to BWCC energies has been suggested [142], which consists in an iterative solution of the amplitude equations (17-33), followed by a single iteration of (17-34) and a final assembly and diagonalization of the effective Hamiltonian matrix, yielding the corrected energy. This correction is, of course, not exact, but in numerous tests and applications it turned out to yield sufficiently accurate results for practical purposes [143][144][145][146][147][148][149][150][151][152][153][154][155][156].…”
Section: Brillouin -Wigner Mr CC Methodsmentioning
confidence: 99%